Glycated Albumin as an Outcome Predictor in Pregnant Women with Diabetes Mellitus: Glycated Albumin sebagai Prediksi Hasil pada Perempuan Hamil dengan Diabetes Melitus - Cut M. Yeni; Mhd. Maqbul M. Lubis; Munawar; Hendra Zuffry (Indonesian Journal of Obstetrics and Gynecology, 2021)
Abstract Objective: To determine the correlation between Glycated Albumin concentrations with the outcome of pregnant women with Type 2 Diabetes Mellitus in Zainoel Abidin Hospital, Banda Aceh. Methods: This was an observational correlational study using a cross-sectional design. Subjects include pregnant women with a history of Type 2 Diabetes Mellitus who are examined for serum GA levels using colorimetric enzymatic methods and the outcomes will be assessed during pregnancy. Data analysis was performed using the ETA test and Receiver Operating Characteristic (ROC) curve. Results: A total of 29 subjects with a mean age of 33.25 years had normal maternal outcome and those with a mean age of 34.92 years had abnormal maternal outcome. Statistically there was a significant correlation between GA levels and the maternal outcome of pregnant women with Type 2 Diabetes Mellitus (p = 0.009) with a moderate degree of negative correlation (r = 0.477). The GA cut-off for pregnancy outcome is 16.77% with a sensitivity and specificity of 76% and 75% respectively. Conclusion: Examination of GA concentration can be used as a predictor to assess maternal outcomes during pregnancy with moderate correlation and a cutoff point of 16.77%. Keywords: diabetes mellitus, glycated albumin, maternal outcome, pregnancy. Abstrak Tujuan: Untuk mengetahui korelasi kadar Glycated Albumin terhadap outcome pada ibu hamil yang menderita diabetes melitus tipe I dan untuk mengetahui berapa kadar Glycated Albumin yang dapat memberikan hasil buruk pada ibu hamil yang menderita diabetes melitus tipe II di RSUD dr. Zainoel Abidin Banda Aceh. Metode: Penelitian ini merupakan studi korelatif observasional menggunakan desain potong lintang. Perempuan hamil dengan riwayat DMT2 akan diperiksan kadar GA serum menggunakan metode enzimatik kolorimetri serta akan dinilai outcome selama kehamilan. Analisis data dilakukan menggunakan uji Eta dan kurva Receiver Operating Characteristic (ROC) dengan tingkat kepercayaan 95%. Hasil: Sebanyak 29 subjek dengan rerata usia 33,25 tahun (hasil normal) dan 34,92 tahun (hasil kelainan). Secara statistik terdapat korelasi yang bermakna antara kadar GA dan outcome ibu penderita DMT2 (p = 0,009) dengan derajat korelasi sedang (r = 0,477) dengan arah korelasi negatif. Titik potong GA terhadap outcome kehamilan adalah 16,77% dengan sensitifitas dan spesisitas secara berurutan 76% dan 75%. Kesimpulan: Pemeriksaan GA dapat dijadikan sebagai prediktor untuk menilai outcome ibu selama kehamilan dengan tingkat korelasi sedang dan titik potong 16,77%. Kata kunci: diabetes melitus, glikasi albumin, hamil, luaran ibu.